Evaluation of the predictive performance of bleeding risk scores in patients with non-valvular atrial fibrillation on oral anticoagulants - Beshir, Semira Abdi; Aziz, Zoriah; Yap, Lok Bin; Chee, Kok Han; Lo, Yoke Lin (Wiley, 2017)
What is known and objective: Bleeding risk scores (BRSs) aid in the assessment of oral anticoagulant-related bleeding risk in patients with atrial fibrillation. Ideally, the applicability of a BRS needs to be assessed, prior to its routine use in a population other than the original derivation cohort. Therefore, we evaluated the performance of 6 established BRSs to predict major or clinically relevant bleeding (CRB) events associated with the use of oral anticoagulant (OAC) among Malaysian patients. Methods: The pharmacy supply database and the medical records of patients with non-valvular atrial fibrillation (NVAF) receiving warfarin, dabigatran or rivaroxaban at two tertiary hospitals were reviewed. Patients who experienced an OAC-associated major or CRB event within 12 months of follow-up, or who have received OAC therapy for at least 1 year, were identified. The BRSs were fitted separately into patient data. The discrimination and the calibration of these BRSs as well as the factors associated with bleeding events were then assessed. Results: A total of 1017 patients with at least 1-year follow-up period, or those who developed a bleeding event within 1 year of OAC use, were recruited. Of which, 23 patients experienced a first major bleeding event, whereas 76 patients, a first CRB event. Multivariate logistic regression results show that age of 75 or older, prior bleeding and male gender are associated with major bleeding events. On the other hand, prior gastrointestinal bleeding, a haematocrit value of less than 30% and renal impairment are independent predictors of CRB events. All the BRSs show a satisfactory calibration for major and CRB events. Among these BRSs, only HEMORR2HAGES (C-statistic = 0.71, 95% CI 0.60-0.82, P <.001) and ATRIA score (C-statistic = 0.70, 95% CI 0.58-0.82, P <.001) show acceptable discrimination performance for major bleeding events. All the 6 BRSs, however, lack acceptable predictive performance for CRB events. What is new and conclusion: To the best of our knowledge, this is the first evaluation study of the predictive performance of these 6 BRSs on clinically relevant bleeding events applied to the same cohort consisting of mainly Asian novel oral anticoagulant users. These BRSs show poor to acceptable predictive performance on OAC-induced major or CRB events. An improvement in the existing BRSs for OAC users is warranted.